Mapping of biotopes in urban areas: A case study of the city of bartın and its environs, Turkey - Yılmaz, Bülent; Gülez, Sümer; Kaya, Latif Gürkan (Academic Journals, 2010)
Biotope mapping is one of the planning elements playing an important role in detection of ecologically valuable areas. It is obligatory to consider urban biotopes in point of protection and management of natural and cultural structure especially in the development processes of urban areas. However, urban planning in Turkey where 75% of the population lives in urban areas is done without considering existing biotopes. For this reason, the cities lose their identity and gradually lose their quality of being a livable environment. In this study, the cultural and semi-natural biotopes in the City of Barti{dotless}n and its environs, one of the smallest provinces of Turkey, were examined. First land use types were determined and later biotope types were classified and mapped. After determining all land usage types, comprehensive mapping method was applied. However, representative mapping method was also used in areas where land usage and biodiversity were similar. Geographical information systems were used to map urban biotopes and store the ecological data. Varieties in land use types and plant species combination were used as indicators in determination of the areas that show ecological differences. A database were formed in order to provide basis for ecological planning approach in urban areas by mentioning plant species found in each biotope. © 2010 Academic Journals. © 2020 Elsevier B.V., All rights reserved.
Keywords: Barti{Dotless}N; Biotope Mapping; Comprehensive Method; Land Uses; Urban Planning